Bodies in the streets : the somaesthetics of city life - Shusterman, Richard (Studies in Somaesthetics, 2019)
Cities are defined by their complex network of busy streets and the multitudes of people that animate them through physical presence and bodily actions that often differ dramatically: elegant window-shoppers and homeless beggars, protesting crowds and patrolling police. As bodies shape city life, so the city's spaces, structures, economies, politics, rhythms, and atmospheres reciprocally shape the urban soma. This collection of original essays explores the somaesthetic qualities and challenges of city life (in Europe, Asia, Africa, and the Americas) from a variety of perspectives ranging from philosophy, urban theory, political theory, and gender studies to visual art, criminology, and the interdisciplinary field of somaesthetics. Together these essays illustrate the aesthetic, cultural, and political roles and trials of bodies in the city streets.